A clinical study of prevalence of helicobacter pylori in patients with gastritis - Rangaswamy, Purushothaman; Rubby, Shaikh Afzal (International Surgery Journal, 2016)
Background: Stomach infections with Helicobacter pylori mainly occur during childhood. If persistent, these may cause chronic gastritis often leading to peptic ulcer disease, later on in life. Ulcer is a sore or hole in the lining of the stomach or duodenum (the first part of the small intestine). Objective was to detect the prevalence of H. Pylori in patients with gastritis. Methods: This study involved 90 patients with gastritis who attended surgical outpatient as well as inpatient department of ESIC Medical college hospital from April 2014 to March 2016. Results: Endoscopy was carried for all patients to diagnose gastritis. Urease and Serum IgG anti H. Pylori antibodies used to detect the presence of H. Pylori in these patients. Ninety patients; 60 males (66.67%) and 30 females (36.33%) were infected with gastritis. The results showed that 53.33% of the patients gave positive results on urease test. The results showed that for screening and determining the clinical features of gastritis, at least one method for H. Pylori are required to give positive result in order to identify an infected patient with H. Pylori. Conclusions: There is an additional aspect to treatment of gastric ulcers, the one of health care providers and patient’s awareness of the cause and most efficient treatments for this medical condition. Ulcers that presented until recently a life-long disease with only symptomatic relieve available, became an easily curable condition, when the right pathway of treatment is chosen.